Clinical experience on patient‐specific quality assurance for CBCT‐based online adaptive treatment plan. Issue 4 (2nd February 2023) - Shen, Chenyang; Chen, Liyuan; Zhong, Xinran; Gonzalez, Yesenia; Visak, Justin; Meng, Boyu; Inam, Enobong; Parsons, David; Godley, Andrew; Jiang, Steve; Cai, Bin; Lin, Mu‐Han
Abstract: Purpose: Ethos CBCT‐based adaptive radiotherapy (ART) system can generate an online adaptive plan by re‐optimizing the initial reference plan based on the patient anatomy at the treatment. The optimization process is fully automated without any room for human intervention. Due to the change in anatomy, the ART plan can be significantly different from the initial plan in terms of plan parameters such as the aperture shapes and number of monitor units (MUs). In this study, we investigated the feasibility of using calculation‐based patient specific QA for ART plans in conjunction with measurement‐based and calculation‐based QA for initial plans to establish an action level for the online ART patient‐specific QA. Methods: A cohort of 98 cases treated on CBCT‐based ART system were collected for this study. We performed measurement‐based QA using ArcCheck and calculation‐based QA using Mobius for both the initial plan and the ART plan for analysis. For online the ART plan, Mobius calculation was conducted prior to the delivery, while ArcCheck measurement was delivered on the same day after the treatment. We first investigated the modulation factors (MFs) and MU numbers of the initial plans and ART plans, respectively. The γ passing rates of initial and ART plan QA were analyzed. Then action limits were derived for QA calculation and measurement for both initial and online ART plans, respectively, from 30 randomly selected patient cases, and were evaluated using the other 68 patient cases. Results: The difference in MF between initial plan and ART‐plan was 12.9% ± 12.7% which demonstrates their significant difference in plan parameters. Based on the patient QA results, pre‐treatment calculation and measurement results are generally well aligned with ArcCheck measurement results for online ART plans, illustrating their feasibility as an indicator of failure in online ART QA measurements. Furthermore, using 30 randomly selected patient cases, the γ analysis action limit derived for initial plans and ART plans are 89.6% and 90.4% in ArcCheck QA (2%/2 mm) and are 92.4% and 93.6% in Mobius QA(3%/2 mm),  respectively. According to the calculated action limits, the ArcCheck measurements for all the initial and ART plans passed QA successfully while the Mobius calculation action limits flagged seven and four failure cases respectively for initial plans and ART plans, respectively. Conclusion: An ART plan can be substantially different from the initial plan, and therefore a separate session of ART plan QA is needed to ensure treatment safety and quality. The pre‐treatment QA calculation via Mobius can serve as a reliable indicator of failure in online ART plan QA. However, given that Ethos ART system is still relatively new, ArcCheck measurement of initial plan is still in practice. It may be skipped as we gain more experience and have better understanding of the system.